Codicological Study of Dawuhan Islamic Manuscripts as Insights into Nusantara Religious Literature - Sidik Fauji; Jamaluddin, Jamaluddin; Affaf Mujahidah; Adi, Brian Trinanda Kusuma (Jurnal Lektur Keagamaan, 2025)
This article presents a codicological study of Islamic manuscripts from Dawuhan Village, Banyumas, Central Java, which houses numerous texts alongside annual ritual heirlooms. As part of broader philological and codicological research, the study focuses on reconstructing the texts and examining the physical features of the manuscripts to illuminate their historical, cultural, and intellectual significance. The analysis reveals thirteen manuscripts comprising thirty-five texts, covering a wide range of Islamic disciplines such as Qur’anic interpretation, fiqh, theology (tauḥīd), Sufism, ethics, and history. These texts are written in Arabic, Pegon (Arabic script for the Javanese language), and Javanese with Arabic interlinear translations. The study classifies the manuscripts into three main formats: Arabic texts, Arabic texts with Pegon interlinear translation, and Javanese texts in Pegon script. Decorative elements are generally minimal, though some manuscripts feature artistic renderings, such as wayang-inspired calligraphic designs of the basmalah. Most manuscripts lack explicit authorship or date, with only one colophon identifying the scribe as a student (santri), and a few mentioning the day, month, and year of creation. The poor condition of the manuscripts including damaged bindings, faded ink and missing pages, calls for urgent preservation through restoration, digitization and improved storage. The Dawuhan manuscripts offer critical insights into the integration of Islamic teachings with Javanese cultural traditions and highlight the diversity of Islamic educational practices in the region. As such, they constitute a valuable resource for religious, linguistic, and cultural studies, warranting further scholarly attention and conservation efforts.